1999
DOI: 10.1038/sj.onc.1203241
|View full text |Cite
|
Sign up to set email alerts
|

Cells with TP53 mutations in low grade astrocytic tumors evolve clonally to malignancy and are an unfavorable prognostic factor

Abstract: It is important to understand how low grade tumors recur and progress to malignant lesions since this dramatically shortens patient survival. Here, we evaluated the concept that malignant progression and poor prognosis of low grade astrocytic tumors are TP53 dependent through clonal expansion of mutated cells. TP53 status was established in primary and recurrent tumors from 36 patients with WHO grade II astrocytic tumors and two tumor types were found. Tumors from 14 patients (39%; type 1) had TP53 mutated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 18 publications
0
44
1
Order By: Relevance
“…Knowledge derived from genetic syndromes (39) and GWAS studies (40,41) has shown that an inherited genetic component may accelerate this process. The fittest cell populations likely establish precancerous clones, although we have little direct evidence to support this process in human GBM because of limitations in detecting the early steps in brain cell transformation (42,43). Divergent genetic alterations in early transformed cells can subsequently give rise to a variety of clones under the selective pressure of the evolutionary ecosystem in the tumor (27)(28)(29)(35)(36)(37).…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…Knowledge derived from genetic syndromes (39) and GWAS studies (40,41) has shown that an inherited genetic component may accelerate this process. The fittest cell populations likely establish precancerous clones, although we have little direct evidence to support this process in human GBM because of limitations in detecting the early steps in brain cell transformation (42,43). Divergent genetic alterations in early transformed cells can subsequently give rise to a variety of clones under the selective pressure of the evolutionary ecosystem in the tumor (27)(28)(29)(35)(36)(37).…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…To further evaluate our hypothesis, we did the same set of transfections with another human glioblastoma cell line, LN229, which is PTEN (mutated in multiple cancers, phospha- (33). These cells showed a trend of NF-B activation similar to that observed in U87MG cells; however, the relative luciferase activity was reduced (Fig.…”
Section: Vol 24 2004 Role Of Shp-2 In Egfr-mediated Nf-b Activationmentioning
confidence: 99%
“…However, the prognostic significance of p53 mutations in LGAs is unclear, with some studies showing it to be associated with malignant progression and shorter progressionfree and overall survival while others have not seen any significant association. 1,6,9,11,15,16 More recently, it has been shown that gemistocytic astrocytomas have a higher number of microglia, with more microglia being present when the fraction of gemistocytes is high. 8 Additionally gemistocytes were seen to be reactive for major histocompatibility complex Class II molecules.…”
mentioning
confidence: 99%